Finansowanie zrównoważonego rozwoju - zasady i dylematy - Famielec, Józefa (Financing sustainable development - principles and dilemmas, 2007)
Sustainable development is capital-intensive and requires considerable resources for environmental protection, especially in the context of transitory periods for incorporation of eco directives, as negotiated by Poland. Significant expenditures are needed that should be financed by entrepreneurs - polluters - in linę with the principle ‘let the polluter pay’. In Poland, polluters do not as yet contribute in fuli to the environmental protection costs. Urgent need arises to develop strategies for financing environmental protection in respective enterprises and sectors, to ensure fulfillment of the deadlines for implementation of EU directives on ecology.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 419-433